2005
DOI: 10.1097/01.ju.0000148374.64478.b5
|View full text |Cite
|
Sign up to set email alerts
|

Primary Lower Urinary Tract Reconstruction for Nonfunctioning Renal Moieties Associated With Obstructing Ureteroceles

Abstract: We believe that primary, single stage, lower urinary tract reconstruction in children with severely compromised or nonfunctioning renal moieties damaged by ureteroceles is superior to upper urinary tract ablative surgery, successfully correcting the obstructive or refluxing pathology with minimal morbidity and risk during long-term followup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 19 publications
0
23
0
2
Order By: Relevance
“…4,31,32 Preservation of associated renal units the ureterocele can put the lower pole or contralateral units at risk of damage by obstructing either unit or the bladder outlet. these conditions are both uncommon, but there is general agreement that the presence of obstruc tion, detected as nonrefluxing or progressive dilation of associated moieties or as an alteration in renal function, mandates timely ureterocele decompression.…”
Section: Key Pointsmentioning
confidence: 99%
“…4,31,32 Preservation of associated renal units the ureterocele can put the lower pole or contralateral units at risk of damage by obstructing either unit or the bladder outlet. these conditions are both uncommon, but there is general agreement that the presence of obstruc tion, detected as nonrefluxing or progressive dilation of associated moieties or as an alteration in renal function, mandates timely ureterocele decompression.…”
Section: Key Pointsmentioning
confidence: 99%
“…Bu gibi olgularda alt üriner sistem cerrahisi gereksiniminin % 16 gibi düşük düzeyde olduğunu bildirenler çalışmalar olduğu gibi uzun dönem izlemlerinde % 64-70 oranında major alt sistem cerrahisi gerektiğini bildiren çalışmalar da vardır (5,10,20,22,31) . Yüzde 75 olguda alt pole reflü olduğu için nonfonksisyonel üst pol eksizyonunun yeterli olmayacağı kanısı yaygındır (13) . Dolayısı ile alt üriner sistemde ektopik yerleşimli üreterosel eksizyonu, mesane tabanı rekonstrüksiyo-nu ve reimplantasyon ile onarım sıklıkla tercih edilen uygulamalardır (15) .…”
Section: Discussionunclassified
“…UTA is the appropriate initial management. Although, some authors have suggested CSR or TR as the first step, 9,21 BLA involves a larger incision, greater technical difficulties, and more hospital days with more reoperation rates. When UTA is not indicated because of ipsilateral high-grade VUR or severely dilated UPU, 15 BLA, especially CSR with ureterocelectomy, is the next option.…”
Section: Commentmentioning
confidence: 97%
“…22,23 The other is the fact that there has been no reported postoperative hypertension and proteinuria in the dysplastic upper pole kidney despite the theoretical risk. 15,21 However, CSR requires reimplantation of the bulky common sheath ureter, often with plication. Although this could be more technically difficult than TR, the reoperation rate of our study was lower than that after TR.…”
Section: Commentmentioning
confidence: 99%